The Effect of Health Service Quality on BPJS Kesehatan Customer Satisfaction With Employee Performance as an Intervening Variable (Case Study on General Poly of Mitra Keluarga Samarinda Clinic) - Wiyandari, Meinnisa (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
The purpose of this study is to examine the effect of health service quality and employee performance on the satisfaction BPJS Kesehatan customers in Mitra Keluarga Clinic. This type of research uses quantitative research using questionnaire method. The population in this research is BPJS Health participants registered at Mitra Keluarga Clinic. Purposive sampling was used to select 273 participants from among all BPJS Health participants registered at Mitra Keluarga Clinic. Data analysis techniques in this study used Partial Least Square (PLS). Healthcare service quality has seven indicators, including waiting time, medicine, effectiveness, soft interaction, hard interaction, equipment condition, and ambient condition. Employee performance has seven indicators, including giving enough time, asking about symptoms, listening, explaining, involving in decisions, treating with care and concern, and taking problems seriously. While customer satisfaction has three indicators, including overall service satisfaction, interest in revisiting, and willingness to provide recommendations to other parties. The results of this study shows that healthcare service quality have a positive and significant relationship on customer satisfaction, employee performance have a positive and significant relationship on customer satisfaction, healthcare service quality have a positive and significant relationship on employee performance, and also healthcare service quality have a significant indirect relationship on customer satisfaction through employee performance.